Effect of Diode Laser Cycloablation in the Treatment of Refractory Glaucoma - Shahid, Furqan (Indus Journal of Bioscience Research, 2025)
Background: In developing countries, limited resources and ophthalmologists hinder glaucoma care. Diode Laser Trans-scleral Cycloablation (DLCA) offers a simple, cost-effective treatment for refractory glaucoma. This study aims to address the insufficient literature on DLCA outcomes. Objectives: To determine the frequency of success of DLCA in reducing intraocular pressure (IOP) in refractory glaucoma. Study Design: Descriptive case series. Settings and Duration: Department of Ophthalmology, LRBT Eye Hospital, Lahore, from 8th May to 7th November 2024. Methodology: Seventy-three patients aged 18–65 years with refractory glaucoma were included. Patients with thin sclera, scleral atrophy, or prior trans-scleral cyclophotocoagulation were excluded. DLCA was performed using an 810 nm laser, with a power of 1500–2000 mW and a 2-second duration. Achieving IOP in range of 8–21 mmHg at one month was considered as scucessful. Results: The mean age of participants was 45.59 ± 11.52 years, with 43 (58.90%) aged 41–65 years. The majority were male (68.49%), with a male-to-female ratio of 2.17:1. DLCA success was achieved in 60 patients (82.19%). Conclusion: DLCA is an effective, rapid, and cost-efficient procedure for managing refractory glaucoma, providing a viable alternative in resource-limited settings.